The evaluation of parents' views related to helping pre-school children gain some universal values - UYANIK, GÜLDEN (ELSEVIER SCIENCE BV, 2011)
Universal values continue their existence along individual's education lives beginning from pre-school period. A qualified pre-school curriculum shapes pre-school children's character, helps them improve their social and emotional skills, and gain them some social values as well as some other academic skills. This study aims to examine parents' views related to helping pre-school children aged between 5 and 6 years gain some universal values. The sampling of the study consists of the parents of 80 pre-school children. Universal Values Teaching Family Form, which was developed by the researchers was used as the instrument for data collection in the study. The results obtained with this study suggest that parents believe that teaching of universal values should start at preschool stage, and some of the universal values which are considered to have priority in teaching were suggested as; honesty, responsibility and respect.
Keywords: Degerler Egitimi; Aile; Okul Oncesi Egitim